Table 3_Harnessing mRNA technology against Fasciola hepatica: Immunological insights from a fatty acid binding protein vaccine.docx - Javier Sánchez-Montejo (22681769) (2025)
mRNA platforms offer a promising strategy to overcome limitations in helminth vaccinology. We used the helminth Fasciola hepatica, which is a major veterinary and zoonotic pathogen for which no licensed vaccine exists, as a test case. We engineered a codon-optimized mRNA encoding the F. hepatica fatty-acid–binding protein (FABP), verified its expression in HEK293T cells, and formulated it in SM-102 lipid nanoparticles (LNPs). BALB/c mice received a prime-boost immunization (3 weeks apart) followed by longitudinal blood and terminal spleen immune profiling by spectral flow cytometry. Immunization induced rapid innate immune activation with marked neutrophil expansion and monocyte maturation, while reducing circulating mature NK cells, consistent with recruitment to lymphoid tissues. Adaptive responses included increased circulating CD8+ T cells dominated by EMRA effectors, expansion of TCRαβ+ double-negative T cells with memory/effector phenotypes, and a reduction in peripherally induced CD25- regulatory T cells. CD4+ T-helper cells showed a shift toward memory/effector subsets, and antigen-specific Th1 and Th2 responses in the spleen were detected only in vaccinated mice. B-cell analysis revealed accelerated maturation of B2 cells with expansion of marginal-zone, follicular, and germinal-center compartments, higher frequencies of class-switched (IgM-) plasma cells, and exclusive detection of anti-FABP IgG in the mRNA-LNP group. These results demonstrate that an mRNA-LNP vaccine encoding F. hepatica FABPs elicits innate immune activation, cytotoxic and helper T-cell immunity, and class-switched humoral responses in mice, supporting its potential as a candidate for F. hepatica vaccination in a future challenge experiment against the infection.